Microcontroller system of hydrogen pulse injection on stellarator Uragan-3М - Gubarev, S.P.; Korovin, V.B.; Listopad, V.M.; Lozin, A.V.; Mironov, Yu.K.; Opaleva, G.P.; Romanov, V.S.; Taran, V.S.; Zamanov, N.V.; Zolototrubova, M.I. (Вопросы атомной науки и техники, 2015)
This paper describes a renewed system of pulse injection of working gas into the vacuum vessel of the stellarator Uragan -3М. The system was designed and fabricated in the Institute of Plasma Physics of NSC “Kharkov Institute of Physics and Technology” and is intended for providing of the fast-acting dosed injection of hydrogen by the given algorithm. A distinctive feature of the developed system is the use of designed microprocessor-based controller to control the operation of the piezoelectric valve. Описана разработанная в Институте физики плазмы ННЦ ХФТИ обновленная система импульсного напуска рабочего газа на установке Ураган-3М. Система предназначена для обеспечения быстродействующего дозированного напуска водорода по заранее заданной программе. Отличительной особенностью системы является использование разработанного микропроцессорного контроллëра для управления работой пьезоэлектрического клапана. Описана розроблена в Інституті фізики плазми ННЦ ХФТІ оновлена система імпульсного напуску робочого газу на установці Ураган-3М. Система призначена для забезпечення швидкодіючого дозованого напуску водню за заздалегідь заданою програмою. Відмінною особливістю системи є використання розробленого мікропроцесорного контролера для управління роботою п'єзоелектричного клапана.